Effect of (–)-epicatechin-3-gallate and (–)-epigallocatechin-3-gallate on the binding of tegafur to human serum albumin as determined by spectroscopy, isothermal titration calorimetry, and molecular docking. Issue 11 (24th July 2019) - Yuan, Lixia; Liu, Min; Shi, Yabo; Yan, Hui; Han, Jun; Liu, Liying
Abstract: Green tea has attracted great interest as a cancer prevention agent. Interactions of tea polyphenols with serum albumin may influence the efficacy of drugs. The interactions of (–)-epigallocatechin-3-gallate (EGCG), (–)-epicatechin-3-gallate (ECG), and tegafur (TF) alone or in combination with human serum albumin (HSA) at pH 7.4 and different temperatures were investigated by spectroscopic methods, isothermal titration calorimetry (ITC), and molecular docking. The binding affinities to HSA were ranked in the order of EGCG > ECG > TF, and the interactions were spontaneous and exothermic. Ternary system studies showed that the presence of one component hindered the binding of another component to HSA. The secondary structures of HSA were slightly altered in the presence of the ligands. Site marking experiments and molecular docking showed that EGCG and ECG mainly bound to subdomain IIA and ΙΙΙA while TF bound to subdomain ΙΙA and ΙB. Results indicated that the existence of ECG and EGCG would influence the binding of TF to HSA and can increase the free concentration of TF. Obtained results would provide beneficial information about possible interference upon simultaneous co-administration of the tea components and drugs. Communicated by Ramaswamy H. Sarma